Estimation Variability, Heritability and Genetic Advance of Mutant Black Rice (M6) - Ahmad Sofian; Nandariyah Nandariyah; Djati Waluyo Djoar; Sutarno Sutarno (Universitas Sebelas Maret, 2019)
A better understanding of variability in plant populations is crucial for crop improvement which plant breeders can use through selection. This study aimed to determine selection criteria for the sixth generation of black rice through genetic variability, heritability value and genetic advance. This research was conducted from March to July 2018 at Pakahan Village, Jogonalan Sub-district, Klaten Regency, Central Java, using a Randomized Complete Block Design (RCBD). The variables observed were plant height, total number of tillers and productive tillers, panicle length, number of seeds per panicle, panicle intensity index, weight per panicle, 1,000 seed weight, seed weight per plant, flowering age, harvest age, plot yield, yield per hectare, rice color and total anthocyanin content. Variance analysis showed that there was a very significant difference (p <0.01) among the genotypes tested for all observed characters indicating variability. In this study, the phenotypic coefficient of variance (PCV) values was relatively higher than the genotypic coefficient of variance (GCV) for all traits. However, GCV values were close to PCV values in some characters such as plant height, flowering age, harvest age, rice color and anthocyanin content which showed a high contribution of genotypic effects to the phenotypic expression of these characters. The high heritability and high average value of genetic advance were indicated in the parameters of plant height, flowering age, harvest age, rice color and anthocyanin content. The characters of plant height, flowering age, harvest age, rice color and anthocyanin content can be used as sixth-generation black rice selection criteria.